Georgia at Work : Assessing the Jobs Landscape - Posadas, Josefina; Makovec, Mattia; Jaef, Roberto Fattal; Gruen, Carola; Ajwad, Mohamed Ihsan (World Bank, Washington, DC, 2018)
Georgia’s reforms over the last two decades have paved the way for the country’s economic transformation by the creation of better jobs and substantial poverty reduction. Despite these positive developments, some important structural challenges persist in relation to jobs. Growth has not created sufficient jobs in Georgia, especially not enough inclusive and high-productivity jobs. This report analyses the main economic forces driving job creation in Georgia, and attempts to answer four questions. First, Chapter 1 investigates whether the enabling environment is conducive to good job outcomes? Second, Chapter 2 investigates how formal sector job creators doing? Third, Chapter 3 investigates how does the Georgian workforce measure up to the needs of employers? Finally, Chapter 4 recommends a set of policy options that can improve jobs outcomes.